ANALISIS PENGAWASAN TERHADAP ORANG ASING MELALUI DATA DARI APLIKASI PELAPORAN ORANG ASING (APOA) PADA KANTOR IMIGRASI KELAS I TPI PEKANBARU - Duta Indra (Nalar: Journal of Pedagogy and Society, 2022)
The number of foreign nationals who stay who do not have a place to live in Pekanbaru City without the supervision of the local Immigration Office in supporting immigration control of foreigners carried out by the Immigration Office Class I TPI Pekanbaru. The purpose of the research is to find out the implementation of immigration control against foreigners through data from the Foreigner Reporting Application, what are the obstacles that hinder the implementation of immigration control against foreigners through data from the Foreigner Reporting Application and the efforts made by the Class I Immigration Office TPI Pekanbaru in increasing awareness the public towards their obligation to report the presence of foreigners through the Foreigner Reporting Application (APOA). The Foreigner Reporting Application (APOA) is that immigration officers do not get complete data on the whereabouts of foreigners, there are some foreigners whose whereabouts are not known by this Foreigner Reporting Application. This is because the socialization related to the Foreigner Reporting Application has not been carried out thoroughly to the public, companies and lodging in the work area of ​​the Pekanbaru Immigration Office. The efforts made to maximize supervision of foreigners through the Foreigner Reporting Application are by maximizing the first socialization regarding the Foreigner Reporting Application to the entire community, companies and inns so that they can carry out their obligations to report the presence and activities of foreigners through the Foreigner Reporting Application. Foreigners, so that immigration officers can carry out maximum supervision of foreigners.